Investigating incidence of fungal contamination in cosmetic tools used by female students of Al-Kufa university in Al-Najaf, Iraq - Manar Kareem Alquraishy,; Rukaya Saad Al-Abeadi,; Ahmed Adnan AL-Khafagi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Fungal can cause a variety of infections such as skin and eye diseases, and infections may occur spread among women due to sharing salon utensils or cosmetic tools. Objective: This study was proceeded to evaluation the fungal contamination in the personal cosmetic tools used by female students of Al-Kufa university in Al-Najaf, Iraq. Methods:120 samples of cosmetic tools were included in this descriptive study. They collected randomly from women which include beauty blender, lipstick, mascara, eyeshadow brush, concealer brush, eyebrow brush and makeup sponge. All the samples were cultured on potato dextrose agar (PDA) and examined macroscopically and microscopically after the incubation by staining in lactophenol. Data were analysed using SPSS 18 software. Results:It was observed that there are seven species of fungi isolated from the different cosmetic tools, which include Mucor spp., Rhizopus spp., Penicilliumspp. ,Aspergillusniger, Candida albicans, Trichophytonmentagrophytes and Aspergillusfumigatus. The major contaminated tools were the beauty blender and makeup sponge samples followed by lipstick and eyeshadow brush. Conclusion:Therefore, we found that cosmetic tools, especially beauty blender, makeup sponge, lipstick and eye shadow brush are contaminated by fungi and need more awareness.